Derivational and Inflectional Morphological Processes in the Song Lyrics of Niki’s Buzz Album - Nabila Putriana Gustin; Christina x (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2026)
This study explores the morphological processes found in the song lyrics of NIKI’s Buzz album. The research focuses on two primary aspects of morphology, including derivation and inflection. As the problem statement, this study aims to examine how these processes are applied in the song lyrics and what functions they serve in shaping meaning and expression. The study is grounded in the theoretical framework proposed by Aronoff and Fudeman, particularly their classification of derivational and inflectional morphology. The researcher used qualitative method to examine the problem. The findings reveal that the album features a variety of morphological processes. Derivational processes identified include affixation, compounding, zero-derivation, blending, and clipping. No data involving acronyms or back-formation were found. For inflectional processes, the lyrics contain affixation, suppletion, and apophony. No instances of reduplication were found in the data. Derivation morphology in the lyrics serves to change lexical categories, alter meanings, and form words with clearer semantic value. Meanwhile, inflectional morphology is used to indicate number, person, case, tense, and aspect, all without altering the base word’s class or core meaning.